Budgetary change in authoritarian and democratic regimes. Issue 6 (17th June 2017) - Baumgartner, Frank R.; Carammia, Marcello; Epp, Derek A.; Noble, Ben; Rey, Beatriz; Yildirim, Tevfik Murat
ABSTRACT: We compare patterns of change in budgetary commitments by countries during periods of democracy and authoritarianism. Previous scholarship has focused almost exclusively on democratic governments, finding evidence of punctuated equilibria. Authoritarian regimes may behave differently, both because they may operate with fewer institutional barriers to choice and because they have fewer incentives to gather and respond to policy-relevant information coming from civil society. By analysing public budgeting in Brazil, Turkey, Malta and Russia before and after their transitions from or to democracy, we can test punctuated equilibrium theory under a variety of governing conditions. Our goal is to advance the understanding of the causes of budgetary instability by leveraging contextual circumstances to push the theory beyond democracies and assess its broader applicability.